Tax Avoidance of Mining Companies From the Return on Assets, Institutional Ownership, and Audit Committee Perspectives - Tjahjani Murdijaningsih; Maratus Solihah; Krisnhoe Sukma Danuta (Journal of Business and Management Review, 2020)
Taxes are the largest state revenue, but tax companies are a burden that can reduce profits received by shareholders. Then in 2019 tax revenue from the mining sector in 2019 experienced a significant decline. Based on this, this study aims to see how the level of profitability of companies, institutional ownership and audit committees affect mining companies in avoiding taxes. By using 19 company samples for the 2016-2018 period, researchers found that profitability and audit committees could increase corporate tax avoidance. whereas institutional ownership has no influence on tax avoidance.